Positioning Spanish-Language and African American Language (AAL) Speakers as Knowledgeable and Valuable Contributors in the Language Arts Classroom. Issue 3 (3rd July 2019) - Morales, P. Zitlali; Hartman, Paul William
Abstract : We utilize positioning theory to analyze language use within two different language program models in elementary language arts classrooms. We explore how the positioning of minoritized languages as valuable facilitates the use of students' home languages in classrooms and allows us to examine the connections between language, identity, and power. Additionally, through the use of positioning theory alongside language learning theory, we recognize the importance of supporting students' heritage language use, including nonstandard language varieties, in classroom settings. In the dual language (DL) classroom, we see how the teacher positions the Spanish language as valuable and worthy of learning. In the English as a Second Language (ESL) classroom, the teacher positions African American Language (AAL) as worthy of study and inclusion in the curriculum and promotes the use of AAL within the poetry unit. Finally, we identify tensions that can emerge for teachers in different sociopolitical contexts within each of these language learning models.